Variant recurrent risk among stroke patients with different CYP2C19 phenotypes and treated with clopidogrel. (September 2015) - Sun, Wenshan; Li, Yongkun; Li, Junrong; Zhang, Zhizhong; Zhu, Wusheng; Liu, Wenhua; Cai, Qiankun; Wang, Xiaomeng; Cao, Liping; Bai, Wen; Fan, Xinying; Ma, Minmin; et al.
Abstract Polymorphisms of CYP2C19 have been associated with variant risk of subsequent cardiovascular events in survivors of myocardial infarction (MI) receiving clopidogrel. This study evaluated the impacts of CYP2C19 polymorphisms on stroke recurrence and other vascular events in a cohort of Chinese patients receiving clopidogrel. From Nanjing Stroke Registry Program, 625 consecutive patients with ischemic stroke were enrolled between May 2008 and April 2010. CYP2C19 variants (*2, *3, and *17) were genotyped. Clinical outcomes were determined with three monthly follow-up. The primary endpoint was a composite of vascular death, non-fatal ischemic stroke, and non-fatal MI. The second endpoint was bleeding events. The median exposure to clopidogrel was 13.2 (interquartile range, 8.9–18.0) months. Primary endpoint was observed in 85 (13.6%) patients and secondary endpoint in 13 (2.1%) patients. Frequencies of CYP2C19*1, *2, *3, and *17 alleles were 61.2, 34.0, 3.8, and 1.0%, respectively, in this patient cohort. CYP2C19 loss-of-function allele (*2 and *3, LOF) carriers were observed with higher risk of subsequent vascular events compared with non-carriers (17.2 versus 8.1%, HR = 2.16, 95% CI: 1.31–3.56, p = 0.003). After adjusted for age, sex, major cardiovascular risk factors, and drug agent, CYP2C19 LOF carrier was independently associated with primary endpoint (HR = 2.31, 95% CI: 1.39–3.84, p = 0.001). No significant association between CYP2C19 gain-of-function (*17, GOF) and clinical events was detected. In Chinese stroke survivors treated with clopidogrel, carriers of CYP2C19 LOF allele may have increased risk of recurrence.